P13 Changes in mitochondrial morphology & distribution during postnatal development. (21st March 2018) - Summers, K; Lin, H; Caputo, M; Suleiman, MS
Abstract : Vulnerability to cardiac ischemia/reperfusion injury (I/RI) changes during postnatal development, with greatest resistance at postnatal day 14 (P14) in rats. The underlying mechanism is currently unknown. We hypothesise that developmental changes in mitochondrial morphology and distribution of the 3 mitochondrial subpopulations – interfibrillar, perinuclear and subsarcolemmal– may be linked to these differences in vulnerability. Hearts from P14 (n=3) and adult (n=3) rats were perfused with Krebs-solution, followed by fixative solution (1% glutaraldehyde, 1% paraformaldehyde), before processing and embedding in EPON epoxy resin for electron microscopy. Images were taken using a Tecnai12 TEM electron microscope, from which areas, widths, lengths and densities of mitochondria from the 3 subpopulations were measured using ImageJ. All 3 mitochondrial subpopulations had statistically significantly larger mean area, lower aspect ratio, and greater roundness in adult compared with P14 hearts. Adult hearts had a significantly higher density of interfibrillar but lower density of perinuclear mitochondria than P14 hearts. There were also differences in subpopulations within each age group. At P14, interfibrillar mitochondria had a greater area but lower roundness in comparison with perinuclear and subsarcolemmal mitochondria, the two of which showed no significant difference from one another. In adults however, only interfibrillar and subsarcolemmal mitochondria showed significant differences in area, whereas all 3 subpopulations differed in roundness. These data demonstrate marked differences in mitochondrial morphology and distribution between P14 and adult hearts. Whether these distinct characteristics are altered differently by an ischaemic insult, thus explaining variations in vulnerability, is not presently known. This is currently under investigation.